Vascular adaptation in athletes: is there an 'athlete's artery'? - Green, D. J.; Spence, A.; Rowley, N.; Thijssen, D. H. J.; Naylor, L. H. (Experimental Physiology, 2012)
Whilst the existence of a specific phenotype characterized as `athlete's heart' is generally acknowledged, the question of whether athletes exhibit characteristic vascular adaptations has not been specifically addressed. To do so in this symposium, studies which have assessed the size, wall thickness and function of elastic, large muscular and smaller resistance arteries in athletes have been reviewed. Notwithstanding the caveats pertaining to cross-sectional comparisons between athletes and`matched' control subjects, these studies reveal increased conduit artery size, including enlargement of epicardial arteries and those supplying skeletal muscle. Evidence that peak limb blood flow responses are enhanced in athletes further suggests that resistance arteries undergo increases in total cross-sectional area. Such increases can be localized to those arteries supplying active muscle leading to speculation, supported by exercise training studies in humans and animal and cellular data, that arterial enlargement is associated with repetitive episodic increases in arterial shear stress which elicit endothelium-mediated remodelling. Such structural remodelling at conduit and resistance artery level may play a role in accommodating the substantial increase in cardiac output apparent in endurance athletes; arterial pressure is not increased at rest or during exercise in athletes (versus control subjects). Arterial wall remodelling also occurs in athletes but, in contrast to the impact of shear stress on remodelling of arterial lumenal dimensions, the impact of endurance athletic status on wall thickness may be a systemic, rather than localized, phenomenon. Finally, the question of whether the arteries of athletes exhibit enhanced function is moot. Somewhat paradoxically, measures of conduit and resistance artery endothelial function may not be enhanced, compared with healthy control subjects. This may relate to the inherent difficulty of improving arterial function which is already normal, or the time course and transient nature of functional change. It may also relate to the impact of compensatory structural remodelling, as arterial lumen size and wall thickness both affect functional responsiveness. In summary, there is clear evidence for an impact of athletic status on arterial structure and function, at least with respect to the impact of endurance training. Arterial adaptation may, to some extent, emulate that evident in the hearts of endurance athletes, and it is tempting to speculate that similar mechanisms may be at play.